CHORIORETINITIS SCLOPETARIA: OCULAR TRAUMA DUE TO FIREARM PELLETS (Journal of Forensic Medicine & Toxicology, 2018)
Penetrating eye injuries are common preventable causes of visual impairment and visual loss. Many eye injuries are related to particular occupations and certain cultures.Chorioretinitis sclopetaria is a rare ophthalmic finding in trauma. We report of a 22-year-old male patient, who suffered a gunshot wound that passed behind his eyes and developed scleral necrosis and uveal fibrosis from sclopetaria induced by indirect trauma.
Keywords: Sclopetaria; Eye; Trauma; Firearm; Pellet; Blunt